INTERCOMPANY PROFITS AND ARB 51. - Perry, Kenneth W. (The Accounting Review, 1963)
Abstract A survey of consolidated financial statement practices conducted by the American Institute of Certified Public Accountants in the mid-fifties pointed up the lack of, and consequently the need for, uniformity in consolidation practices. In an apparent attempt to get some degree of uniformity in the consolidation area the Institute's Committee on Accounting Procedure in the late fifties issued Accounting Research Bulletin No. 51. While only time will tell whether the recommendations of the Committee are widely adopted in practice, they have already had, in this writer's opinion, far-reaching effects upon the teaching of consolidations. The Bulletin has had and will undoubtedly continue to have a tremendous influence on teaching in such areas as what to consolidate, when to consolidate, and how to consolidate. Its greatest impact, however, from the teaching standpoint has probably been felt in the area of intercompany profit transactions.